Effects of maturation on the magnitude and direction of asymmetry in jumping and change of direction speed in young elite football players - Gonzalo-Skok, O.; Bishop, C. (The Journal of Strength and Conditioning Research, 2025)
Physical performance is often affected by maturation in young athletes and provides an interesting challenge to optimize performance. The present study analyzed whether maturation affects directional dominance, chronological age, body mass, and biological age predictors and assessed between chronological or biological age-group differences in young footballers. One hundred eight elite male players (U-15 to U-19) were tested on bilateral vertical and unilateral vertical and horizontal jumping, sprinting (40 m), and change of direction (COD) ability over single and multiple CODs (times and the percentage-based COD deficit [%CODD]). Almost half of the players (45%) at post-peak height velocity (PHV) showed consistency in the direction of asymmetry (jumping and COD). Ten-meter sprint time was the main predictor to explain the %CODD. Standing height affects unilateral horizontal jumping, and peak speed and unilateral horizontal jumping were the main predictors for unilateral vertical jumping. Post-PHV reported significantly (p < 0.05, effect size [ES] = 0.76-1.50) greater vertical and horizontal jumping, and linear and COD speed performance than mid-PHV. Significant differences (p < 0.05) in jumping, sprinting, and COD performance were found between U-15 and the rest of groups. Furthermore, the U-16 group showed a significant difference (p < 0.05) to the U-19 (for peak speed) and U-18 groups (for 40-m sprint and peak speed). Significantly (p = 0.04, ES = 0.47) lower %CODD asymmetries were found in mid-PHV compared with post-PHV. The study highlights the impact of maturation on the direction of asymmetry, tending to show the same weak side as maturation increases (i.e., older, and more experienced and mature players). Finally, decreasing between-limbs asymmetry should be considered during maturation, especially as greater football specialization.